Crystal structure and photophysical properties of a novel polyoxomolybdate porphyrin. Issue 12 (9th November 2020) - Chen, Wen-Tong
Abstract : A novel polyoxomolybdate with a diprotonated porphyrin as counter‐cation is reported. The compound shows a red photoluminescence emission in N, N ‐dimethylformamide (DMF) solution. Abstract : A novel polyoxomolybdate with a diprotonated porphyrin as counter‐cation, namely, 5, 10, 15, 20‐tetrakis(4‐carboxyphenyl)‐21 H, 22 H, 23 H, 24 H ‐porphine(2+) hexamolybdate(VI) pentahydrate, (C48 H32 N4 O8 )[Mo6 O19 ]·5H2 O or (H2 TCPP)[Mo6 O19 ]·5H2 O, I, was prepared via the hydrothermal reaction of MoCl5, 5, 10, 15, 20‐tetrakis(4‐carboxyphenyl)‐21 H, 23 H ‐porphine (TCPP) and distilled water. The crystal structure of hydrated polyoxometalate (POM) salt I was characterized by single‐crystal X‐ray diffraction. The compound is characterized by an isolated (zero‐dimensional, 0D) structure, because it cannot extend via covalent bonds. The structure contains one [Mo6 O19 ] 2− anion, one (H2 TCPP) 2+ cation and five lattice water molecules. Each of the Mo 6+ ions is six‐coordinated and displays a distorted octahedral motif. The (H2 TCPP) 2+ cation displays a distorted saddle motif. A three‐dimensional (3D) supramolecular framework is formed via hydrogen‐bonding interactions. The compound shows a red photoluminescence emission.